Bibliometric Analysis of Research Trends on Completeness Of Electronic Health And Medical Record Filling By Health Workers - Ramadhan, Fadlan; Noor, Zairin; Bakhiransyah, M.; Arifin, Syamsul; Marlinae, Lenie (Universitas Malahayati, 2025)
ABSTRACT The completeness of electronic health and medical record filling by health workers is a fundamental aspect that impacts the overall quality and efficiency of healthcare systems. As the use of electronic health records (EHRs) becomes increasingly prevalent, understanding research trends related to the completeness of these records is crucial. This bibliometric analysis seeks to provide an in-depth examination of the research landscape concerning EHR completeness by analyzing publication trends, geographical contributions, journal types, and research topic networks. Utilizing bibliometric tools such as VOSviewer, the study spans from 2019 to 2024, offering insights into the evolution of research in this field. The results reveal a notable increase in publication volume over the years, with a significant peak in 2022, indicating a growing academic interest in this subject. The United States and South Africa are identified as major contributors, while other countries like Indonesia and Brazil also show substantial research activity. The majority of the research is published in the form of research articles, although literature reviews, books, and conference papers also contribute to the body of work. Key research clusters identified include themes on the accuracy and completeness of records, factors influencing system quality, and adherence to EHR usage. Overlay and density visualizations illustrate an evolving focus within the research community, highlighting increased attention to quality factors and the challenges related to EHR system implementation and adherence. This analysis provides valuable insights into current research trends, emphasizing the need to address existing gaps and integrate findings from various research clusters. Future research should focus on exploring underrepresented areas and combining insights across different domains to enhance the overall effectiveness of EHR systems. By addressing these gaps, researchers can contribute to improving data entry processes and system implementation, ultimately leading to better healthcare outcomes. Keywords: Electronic Health Records, Completeness, Bibliometric Analysis, Research Trends, Health Workers